CCAT-prime Collaboration: Science Goals and Forecasts with Prime-Cam on the Fred Young Submillimeter Telescope - CCAT-Prime Collaboration; Manuel Aravena; Jason E. Austermann; Kaustuv Basu; Nicholas Battaglia; Benjamin Beringue; Frank Bertoldi; Frank Bigiel; J. Richard Bond; Patrick C. Breysse; Colton Broughton; Ricardo Bustos; et al. (The Astrophysical Journal Supplement Series, 2022)
We present a detailed overview of the science goals and predictions for the Prime-Cam direct-detection camera–spectrometer being constructed by the CCAT-prime collaboration for dedicated use on the Fred Young Submillimeter Telescope (FYST). The FYST is a wide-field, 6 m aperture submillimeter telescope being built (first light in late 2023) by an international consortium of institutions led by Cornell University and sited at more than 5600 m on Cerro Chajnantor in northern Chile. Prime-Cam is one of two instruments planned for FYST and will provide unprecedented spectroscopic and broadband measurement capabilities to address important astrophysical questions ranging from Big Bang cosmology through reionization and the formation of the first galaxies to star formation within our own Milky Way. Prime-Cam on the FYST will have a mapping speed that is over 10 times greater than existing and near-term facilities for high-redshift science and broadband polarimetric imaging at frequencies above 300 GHz. We describe details of the science program enabled by this system and our preliminary survey strategies.